Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn - A. Schlegel; D. Bond (Kansas Agricultural Experiment Station Research Reports, 2019)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2018, N applied alone increased yields by 76 bu/a, whereas P applied alone increased yields by more than 17 bu/a. Nitrogen and P applied together increased yields up to 169 bu/a. This is 26 bu/a more than the 10-year average, where N and P fertilization increased corn yields up to 143 bu/a. Application of 120 lb/a N (with highest P rate) produced 97% of the maximum yield in 2018, which is slightly greater than the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields 9 bu/a. Average grain N content reached a maximum of 0.6 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu). At the highest N and P rate, apparent fertilizer nitrogen recovery in the grain (AFNRg) was 43% and apparent fertilizer phosphorus recovery in the grain (AFPRg) was 62%.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated corn; long-term fertility; nutrient removal